2013
DOI: 10.5194/acp-13-6391-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land convection on temperature diurnal variation in the tropical lower stratosphere inferred from COSMIC GPS radio occultations

Abstract: Following recent studies evidencing the influence of deep convection on the chemical composition and thermal structure of the tropical lower stratosphere, we explore its impact on the temperature diurnal variation in the upper troposphere and lower stratosphere using the high-resolution COSMIC GPS radio-occultation temperature measurements spanning from 2006 through 2011. The temperature in the lowermost stratosphere over land during summer displays a marked diurnal cycle characterized by an afternoon cooling.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 70 publications
5
34
1
Order By: Relevance
“…To explain this feature, Liu and Zipser (2009) suggested two hypotheses: (1) in situ ice formation when deep convection generates gravity waves that lift and cool the tropopause (Potter and Holton, 1995;Sherwood and Dessler, 2001) leading to the dehydration of the TTL in the late afternoon, a process known as "freeze and dry"; and (2) "ice geysers" that can directly inject ice crystals formed in the adiabatically cooled core of the overshoot turrets potentially hydrating the TTL after being sublimated (Corti et al, 2008;Khaykin et al, 2009). Both hypotheses result in a cooling of the TTL, which is consistent with the results of Khaykin et al (2013). Following Liu and Zipser (2009), we investigate the diurnal H 2 O variability in the tropics using an extended and improved MLS data set described in the following section.…”
Section: Convective Intensity Proxies Of Opfssupporting
confidence: 69%
See 3 more Smart Citations
“…To explain this feature, Liu and Zipser (2009) suggested two hypotheses: (1) in situ ice formation when deep convection generates gravity waves that lift and cool the tropopause (Potter and Holton, 1995;Sherwood and Dessler, 2001) leading to the dehydration of the TTL in the late afternoon, a process known as "freeze and dry"; and (2) "ice geysers" that can directly inject ice crystals formed in the adiabatically cooled core of the overshoot turrets potentially hydrating the TTL after being sublimated (Corti et al, 2008;Khaykin et al, 2009). Both hypotheses result in a cooling of the TTL, which is consistent with the results of Khaykin et al (2013). Following Liu and Zipser (2009), we investigate the diurnal H 2 O variability in the tropics using an extended and improved MLS data set described in the following section.…”
Section: Convective Intensity Proxies Of Opfssupporting
confidence: 69%
“…The positive D-N, however, is consistent with the diurnal temperature cycle as presented by Khaykin et al (2013), and attributed to non-migrating tides and convective updraught of adiabatically cooled air, of maximum amplitude in the LS. H 2 O potentially turns into ice with the afternoon temperature drop, and then sublimates the next morning when the temperature rises.…”
Section: Hydrating-dehydrating Processessupporting
confidence: 58%
See 2 more Smart Citations
“…In contrast to that, Randel et al (2015) found that enhanced tropospheric convection within Asian and North American monsoons leads to reduced stratospheric water vapour. While upscaling the overshooting events and quantifying their net effect on water vapour remains a difficult task, various space-borne observations suggest that the most vigorous convection, capable of direct transport of material into the lower stratosphere, is mostly restricted to the tropical land regions (Liu and Zipser, 2005;Ricaud et al, 2009;Iwasaki et al, 2010;Bergman et al, 2012;Khaykin et al, 2013a;Carminati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%